What Is in Your Output Gap? : Unified Framework and Decomposition into Observables - Andrle, Michal (IMF Working Papers; Working Paper ;, 2013)
This paper discusses several popular methods to estimate the 'output gap'. It provides a unified, natural concept for the analysis, and demonstrates how to decompose the output gap into contributions of observed data on output, inflation, unemployment, and other variables. A simple bar-chart of contributing factors, in the case of multi-variable methods, sharpens the intuition behind the estimates and ultimately shows 'what is in your output gap.' The paper demonstrates how to interpret effects of data revisions and new data releases for output gap estimates (news effects) and how to obtain more insight into real-time properties of estimators.